A new breed of Islamic accountants and their role in Islamic institutions - Nik Abdul Ghani, Nik Abdul Rahim; Laluddin, Hayatullah; Mat Zain, Mat Nor; Zakaria, Zamzuri (American-Eurasian Network for Scientific Information (AENSI), 2012)
Accountants and accounting have played a very crucial role in Muslim societies. Accountants who were known as al-Katib or al-Muhasib, held very prestigious positions in Islamic institutions. The purpose of this paper is to discuss accountability of accountants from Islamic perspective. Then, this paper attempts to explain the role of Islamic accountants as a new demanded profession in Islamic institutions in order to meet the objective of Shariah.